The globalization of crime: a transnational organized crime threat assessment (UNODC, 2010)
"In The globalization of crime: a transnational organized crime threat assessment, UNODC analyses a range of key transnational crime threats, including human trafficking, migrant smuggling, the illicit heroin and cocaine trades, cybercrime, maritime piracy and trafficking in environmental resources, firearms and counterfeit goods. The report also examines a number of cases where transnational organized crime and instability amplify each other to create vicious circles in which countries or even subregions may become locked. Thus, the report offers a striking view of the global dimensions of organized crime today."